1998
DOI: 10.1002/chin.199834178
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: 4H,8H‐Bis‐(1,2,5‐oxadiazolo)[3,4‐b:3′,4′‐e]pyrazine and Some Derivatives.

Abstract: 4H,8H-Bis-(1,2,5-oxadiazolo) [3,4-b:3',4'-e]pyrazine and Some Derivatives. -Several chemical transformations of the title bisoxadiazolopyrazine (I) are studied. Compound (I) does not undergo direct nitration in the presence of nitric acid. Instead, an oxidative dehydrogenation or destruction of one furazane cycle is observed. Nitration as well as nitrosylation products (XVII) and (XIX), however, are obtained by reaction of the dipotassium salt of compound (I) with dinitrogentetra-and pentoxide. The weak NH-aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As illustrated in Scheme 1, the targeted three compounds were obtained by the reactions of the respective nitrobenzene derivatives with DFP or 4-amino-difurazano[3,4-b:3 0 ,4 0 -e]pyrazine (ADFP) in acetonitrile. The synthetic route was according to the previously reported procedure by Tselinskii et al 15 It was observed that the reactivity of DFP and 1-chloro-2,4dinitrobenzene was lower than that of 2-chloro-1,3,5trinitrobenzene. A supposed reason is that the electrophilicity of 2-chloro-1,3,5-trinitrobenzene is stronger than 1-chloro-2,4dinitrobenzene.…”
Section: Synthesis Aspectsmentioning
confidence: 99%
“…As illustrated in Scheme 1, the targeted three compounds were obtained by the reactions of the respective nitrobenzene derivatives with DFP or 4-amino-difurazano[3,4-b:3 0 ,4 0 -e]pyrazine (ADFP) in acetonitrile. The synthetic route was according to the previously reported procedure by Tselinskii et al 15 It was observed that the reactivity of DFP and 1-chloro-2,4dinitrobenzene was lower than that of 2-chloro-1,3,5trinitrobenzene. A supposed reason is that the electrophilicity of 2-chloro-1,3,5-trinitrobenzene is stronger than 1-chloro-2,4dinitrobenzene.…”
Section: Synthesis Aspectsmentioning
confidence: 99%
“…4,8-Di(2,4,6-trinitrophenyl) difurazano [3,4-b:3′,4′-e]pyrazine (TNBP, Figure 1 ), first synthesized by Russian scientists in the 1990s [ 1 ], has become an ideal choice for ultra-high temperature heat-resistant energetic materials due to its excellent heat resistance and good detonation performances (T d : 415 °C, D: 7874 m/s, P: 28.2 GPa). Currently, the morphology of TNBP synthesized by the process has obvious angularity and uneven particle size distribution, affecting the product performances [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 H ,8 H -Difurazano­[3,4- b :3′,4′- e ]­pyrazine (DFP) is an important heat-resistant explosive intermediate with good thermal stability up to 279 °C. , It also exhibits high detonation properties due to abundant C–N, N–O, and CN bonds in the molecule contributing to its high enthalpy of formation . It can be easily derivatized to give heat-resistant explosives including 4,8-bis­(2,4,6-trinitrophenyl)­difurazano­[3,4- b :3′,4′- e ]­pyrazine ( 1 ), high-performing explosives including 4,8-dinitrodifurazano­[3,4- b :3′,4′- e ]­pyrazine ( 2 ) and 4,8-dinitraminodifurazano­[3,4- b :3′,4′- e ]­pyrazine ( 3 ), and other important compounds (Figure a). , …”
Section: Introductionmentioning
confidence: 99%
“…Current literature reports two major routes to synthesize DFP. One is a two-step synthesis using 3,4-diaminofurazan (DAF) and dichloroglyoxime (DCG) (Figure b) . In a reproduction of this method, we can only achieve a low yield of 16% compared with the literature yield of 40% in the first step.…”
Section: Introductionmentioning
confidence: 99%